Lexical Variants of Fixed Word Combinations in Political-Social Press Releases - Bryła-Lech, Joanna (Respectus Philologicus, 2012)
Fixed word combinations and their modifications are frequently used by journalists in press releases of a political and/or social profile. Analyzing the source material gathered from “Gazeta Wyborcza” in 2001, I found many lexical variants of phrasemes and proverbs.The most interesting modifications appeared in the headlines. This article describes a few such examples.Fixed word combinations make it easier for senders of political-social announcements to express their thoughts indirectly. They can be used to convey irony, mockery, or aversion towards a person or the subject of the statement in a veiled way. The proper understanding (i.e., in accordance with the sender’s intentions) of such a constructed announcement often requires some intellectual effort from the reader. It is a kind of game. Interpreting the metaphorical sense causes a relationship to form between the participants of the communicative process.Changeable modifications appear as a result of the replacement of one component by a different word, which from the sender’s point of view is more attractive than the one in the base form (Bąba 1989, p. 54). This leads to the appearance of so-called lexical variants. Most frequently, these units are not fixed in the Polish language, but are created especially for the needs of a certain text. They enable the meaning of a phraseme or proverb to be matched to the content of the article, which constitutes the context of its usage. They usually narrow the meaning.The modified phrasemes and proverbs attract the reader’s attention, convincing him of the sender’s views. The language of politics and the media is the language of manipulation and persuasion. Fixed word combinations are very important language devices that facilitate an effective influence on the reader/receiver.
Keywords: phraseology; modifications; manipulation; linguistic practical jokes; modern press